2008
DOI: 10.1113/jphysiol.2007.144105
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of axoplasmic transport induces mechanical sensitivity in intact rat C‐fibre nociceptor axons

Abstract: Peripheral nerve inflammation can cause axons conducting through the inflamed site to become mechanically sensitive. Axonal mechanical sensitivity (AMS) of intact axons may explain symptoms in a diverse number of conditions characterized by radiating pain evoked by movements of the affected nerve. Because nerve inflammation also disrupts axoplasmic transport, we hypothesized that the disruption of axoplasmic transport by nerve inflammation could cause the cellular components responsible for mechanical transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 37 publications
3
58
1
Order By: Relevance
“…This proportion is comparable with the number of mechanically sensitive C-fiber axons found by Dilley and Bove (2008) (3 of 43), who demonstrated that blocking axoplasmic transport increases the prevalence of axonal mechanosensitivity proximal of the block (to 11 of 36). The von Frey threshold of the individual axon was always much higher than that of the RF.…”
Section: Axonal Mechanosensitivitysupporting
confidence: 79%
“…This proportion is comparable with the number of mechanically sensitive C-fiber axons found by Dilley and Bove (2008) (3 of 43), who demonstrated that blocking axoplasmic transport increases the prevalence of axonal mechanosensitivity proximal of the block (to 11 of 36). The von Frey threshold of the individual axon was always much higher than that of the RF.…”
Section: Axonal Mechanosensitivitysupporting
confidence: 79%
“…15,23 Maintaining healthy nerve function using neurodynamic techniques may occur by promoting uninterrupted axonal transport, thereby preventing deposition of mechanosensitivity elements, the presence of which results in pain and limited neural movement. 8,22 In the early stages of stretch injury or compression, the ability to prevent or at least reduce edema may prevent or slow the inhibition of blood flow, 15,23 thus preventing the sequelae leading to impaired axonal transport, 18,20 demyelination, 11,24 loss of elasticity due to fibrosis or adhesions, 46,63 and ultimately to alteration in nerve structure and function. 19,24,27 The ability to promote fluid dispersion using range of motion may provide a means to break the cycle of edema formation leading to fibrosis, 50 which may in turn lead again to edema formation.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders include compression syndromes or other neuromuscular conditions that may be accompanied by neuropathic pain. [1][2][3][4][5] Damaged nerves exhibit predictable pathophysiological responses including impaired nerve mobility, [6][7][8][9] increased mechanosensitivity, 8,10 impaired nerve conduction, [11][12][13] nerve tissue ischemia, 14,15 axonal transport inhibition, [16][17][18][19][20][21][22] and intraneural edema. 15,[23][24][25][26][27][28] Impaired nerve mobility and increased mechanosensitivity provide the basis for existing studies of neurodynamic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…3,35 Neurodynamic techniques may promote healthy nerve function by promoting reduced oedema and changing intraneural pressure, which lead to improvement in axonal transport and prevention of the deposit of mechanosensitivity factors that result in pain and limitations in neural movement. 46,47 During the initial stages of neural tension or compression injury, the prevention or reduction of oedema may limit compromise of blood flow. The promotion of intraneural fluid dispersion through the incorporation of lower limb movement may provide a mechanism to disrupt the cycle of oedema formation and the subsequent consequences that contribute to fibrosis.…”
Section: Conflicts Of Interestmentioning
confidence: 99%